(3fXQjGJ (B- (3JWHjbGJs - (3OQhjT ceGd GdOjf YHO GdQMeGfs; (3bOQj SjO eQSj s ((3GdbGgQIs (3eQcR GdcJGH ddfTQs, 2002)
(3GdbjdS h GdJbhje aj GdjO , h WQb JMdjd GdeHGQGI Ydi hLg GdNUhU, h eQGMd JfajO GdGNJHGQGJ h cjajI JWHjbgG h GNJHGQGJ GdCOGA MGQS GdeQei aj cQI GdjO h aj GdCNjQ GdefGaGSI chSjdI ef hSGFd GdJbhje(B.s
Keywords: (3cQI GdjOs